Impact of Redhat IPv6 router on heterogeneous host connections - Syed Mohamed, Sulaiman; Buhari, M. I.; Badhusha, Akbar (JOHN WILEY & SONS LTD, 2007)
Internet's popularity has been expanding on dramatic pace and the number of people getting connected to it multiplies regularly. With this high demand, the current Internet Protocol (IPv4) has reached its limits. The next generation Internet Protocol version6 (IPv6) has been incorporated into various operating systems. The motivation behind this work is how well IPv6 co-operates with various operating systems. The performance of the IP stack, together with the behaviour of the OS greatly affects the efficiency of network applications built on top of it. The acceptance of IPv6 implementations on various operating systems heavily relies on the end-user performance. In this paper, we propose to analyse these various IPv6 implementations for its host and router-level supports. In this paper, we investigate the impact of Redhat-based IPv6 router on IPv6 stacks of three different operating systems namely, Windows200.3, Redhat Linux 9.0 (Redhat9.0) and FreeBSD4.9. Copyright (C) 2006 John Wiley & Sons, Ltd.